A multicentric study regarding the use of hormone therapy during female mid-age (REDLINC VI). (August 2014) - Blümel, J. E.; Chedraui, P.; Barón, G.; Benítez, Z.; Flores, D.; Espinoza, M. T.; Gomez, G.; González, E.; Hernández, L.; Lima, S.; Martino, M.; Montaño, A.; et al.
Abstract Background Menopausal hormone therapy (HT) has shown benefits for women; however, associated drawbacks (i.e. risks, costs, fears) have currently determined its low use. Objective To determine the prevalence of current HT use among mid-aged women and describe the characteristics of those who have never used, have abandoned or are currently using HT. In addition, reasons for not using HT were analyzed. Method This was a cross-sectional study that analyzed a total of 6731 otherwise healthy women (45–59 years old) of 15 cities in 11 Latin American countries. Participants were requested to fill out the Menopause Rating Scale (MRS) and a questionnaire containing sociodemographic data and items regarding the menopause and HT use. Results The prevalence of current HT use was 12.5%. Oral HT (43.7%) was the most frequently used type of HT, followed by transdermal types (17.7%). The main factors related to the current use of HT included: positive perceptions regarding HT (odds ratio (OR) 11.53, 95% confidence interval (CI) 9.41–14.13), being postmenopausal (OR 3.47, 95% CI 2.75–4.36) and having a better socioeconomic level. A total of 48.8% of surveyed women had used HT in the past, but abandoned it due to symptom improvement or being unconcerned; fear of cancer or any other secondary effects were also reported but in less than 10%. Among women who had never used HT, 28% reported the lack of medical prescription as the main reason, followed by the absence of symptoms (27.8%). Among those reporting lack of prescription as the main reason for not using HT, 30.6% currently had severe menopausal symptoms (total MRS score > 16); 19.5% of women were using alternative 'natural' therapies, with 35.1% of them displaying severe menopausal symptoms as compared to a 22.5% observed among current HT users. Conclusion The use of HT has not regained the rates observed a decade ago. Positive perceptions regarding HT were related to a higher use. Lack of medical prescription was the main reason for not using HT among non-users, many of whom were currently displaying severe menopausal symptoms.